The Implementation of Collaborative Drug Administration Intervention in The Emergency Room of Hospital X at Banda Aceh - Ruzanna, Jihan Syifa'; Syarif, Hilman; Aklima, Aklima (Journal Of Health Science (Jurnal Ilmu Kesehatan), 2025)
Medication safety is a main focus to maintain patient safety. Recent studies show that almost 50% of adverse incidents in the global health system are rooted in inaccuracy in drug administration. This study aimed to determine the implementation of collaborative interventions for drug administration in the Emergency Room of X Hospital in Banda Aceh. This quantitative descriptive study, using a cross-sectional approach, used a total sampling technique to select 58 respondents. Data was collected through direct observation of drug administration practices and analyzed using descriptive statistical tests. The results showed that the implementation of the principle of the seven rights of drug administration in the Emergency Room of Hospital X in Banda Aceh was in the good category (72.4%); with the implementation of drug administration to the right patient (91.4%), right drug (96.6%), right dose (100%), right route (100%), right time (94.8%), right documentation (93.1%), and right information (96.6%). In conclusion, nurses in the Emergency Room of Hospital X have applied the seven rights of drug administration principle. However, more effort is required to increase nurse adherence to this principle, especially in verifying patient identity and providing drug information. It is expected that hospitals can conduct continuous planning, monitoring, evaluation, and supervision to strengthen the implementation of the seven rights principles of drug administration and to ensure patient safety.